Trees: Kings of the Forest - Andy Hirsch (First Second, 2018)
Every volume of Science Comics offers a complete introduction to a particular topic--dinosaurs, coral reefs, the solar system, volcanoes, bats, flying machines, and many more. These gorgeously illustrated graphic novels offer wildly entertaining views of their subjects. Whether you're a fourth grader doing a natural science unit at school or a thirty-year-old with a secret passion for airplanes, these books are for you! This volume: In Trees we follow an acorn as it learns about its future as Earth's largest, longest-living plant. Starting with the seed's germination, we learn about each stage until the tree's maturation, different types of trees, and the roles trees take on in our ecosystem.
Keywords: Narrative Non-Fiction -- Narrative Non-Fiction